The Effect of the STEM Learning Model on Student’s Critical Thinking in Indonesia: Meta-Analysis - Baso Intang Sappaile; Abdul Rahman; Ilwandri Ilwandri; Tomi Apra Santosa; Ichsan Ichsan; Jedithjah Naapia Tamedi Papia (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of STEM learning models on students' critical thinking skills in Indonesia. This type of research is a meta-analysis. Data sources came from 13 national and international journals. Data sources were searched from Google Scholar, ScienceDirect, ProQuest, Eric Journal, and Springer. The process of selecting data sources was carried out systematically and thoroughly. The collection technique was direct observation. Inclusion criteria in the study are 1) Data sources come from journals and proceedings indexed by SINTA, Scopus, and WOS; 2) The type of research is experimental or quasi-experimental; 3) Research related to the STEM model on critical thinking skills; 4) Journal publications 2015-2023; 5) Research has data sources that can be calculated effect size (ES) values. The results showed the average effect size (ES) value of 0.968 high criteria. This finding shows that the STEM model has a very large influence on students' critical thinking skills. The STEM model helps students be more creative and innovative in the learning process